(untitled) (KYAMC Journal, 2021)
Introduction: Nosocomial infections have been described as an important issue among intubated patients which leads to significant morbidity and mortality. The pattern of microbiological colonization and antibiotic resistance are much valuable in this regard. Objectives: The aim of present study was to determine the pattern of aerobic bacteria isolated from endotracheal tubes in adult patients and determination of their antimicrobial susceptibility patterns. Materials and Methods: Specimens were collected from tracheal tubes of patients with endotracheal aspiration and microbiological investigations were done. The isolated bacteria were identified by using standard cultural and biochemical tests. Then antibiotic susceptibility testing was performed on the isolates by disc diffusion method according to clinical and laboratory Standards Institute (CLSI) guideline. Results: Among 104 participants 68 (65.4%) were female and 36 (34.6%) were male. Most of the patients were in the age group of 71-80 years (48.0%). From 104 positive growths, both Gram positive and Gram negative organisms were found. Maximum samples showed growth of gram negative organism. Antimicrobial susceptibility testing revealed that the most resistant Gram negative isolate was Klebsiella with highest resistance against Vancomycin (40.4%) and which showed highest sensitive against Cefotetan, Cefoxitin and Norfloxain (39.4%). Conclusions: It may be concluded that this study indicates the emergence of antibiotic resistant infections in the studied hospital. So, there is a need to improve the effectiveness of integrated infection control programs to control and manage nosocomial infections caused by highly resistant organisms. KYAMC Journal. 2021;12(3): 153-160